2018
DOI: 10.1002/acr.23430
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect Modifiers of the Association Between Physical Activity Patterns and Joint Symptoms in Middle‐Aged Women

Abstract: ObjectiveTo examine whether body mass index (BMI), menopausal status, and hormone therapy (HT) use modify the association between physical activity (PA) patterns throughout middle age and the incidence and prevalence of joint symptoms in women in later middle age.MethodsData were from 6,661 participants (born 1946–1951) in the Australian Longitudinal Study on Women's Health. Surveys, with questions on joint pain and stiffness, PA, height and weight, menopausal symptoms, and HT use, were completed every 3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Regarding the independent associations between potential confounding variables and musculoskeletal pain our results showed that the level of physical activity (in this case, physical inactivity) was associated with a higher number of body areas with pain in the last 7 days, as older age and higher severity of depressive symptoms were associated with pain in the knee and thigh regions in the last 12 months. These results are similar to those of previous studies where depression, physical inactivity, and age were potential risk factors for musculoskeletal pain in postmenopausal women 39–41 . Concerning BMI, we observed the same, where a higher value was associated with more multi‐located pain in the last 7 days.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the independent associations between potential confounding variables and musculoskeletal pain our results showed that the level of physical activity (in this case, physical inactivity) was associated with a higher number of body areas with pain in the last 7 days, as older age and higher severity of depressive symptoms were associated with pain in the knee and thigh regions in the last 12 months. These results are similar to those of previous studies where depression, physical inactivity, and age were potential risk factors for musculoskeletal pain in postmenopausal women 39–41 . Concerning BMI, we observed the same, where a higher value was associated with more multi‐located pain in the last 7 days.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the cross-sectional nature of this finding, it is unclear whether worse pain or lower levels of physical activity comes first. However, a recent study suggests that maintaining at least low levels of physical activity throughout middle age is associated with a lower incidence of later joint symptoms 12 , underscoring the importance of physical activity for patients with knee OA. We are unaware of previous studies investigating the impact of baseline physical activity level on pain relief from exercise therapy in patients with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has a positive impact on physical function and disease-related symptoms such as pain [7][8][9][10]. Furthermore, physical activity is a strong, evidencebased measure for primary and secondary prevention of osteoarthritis, above all in the knee [11][12][13]. Still, many patients do not comply with exercise recommendations in the long term although they know about and have experienced the positive effects of physical activity and training [14][15][16].…”
Section: Introductionmentioning
confidence: 99%